2009
DOI: 10.1007/s11099-009-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Photorespiration and photoprotection of grapevine (Vitis vinifera L. cv. Cabernet Sauvignon) under water stress

Abstract: In order to investigate the photoprotective function of photorespiration in grapevine under water stress, potted grapevines (Vitis vinifera L. cv. Cabernet Sauvignon) were randomly divided into three uniform groups for well-watered [watered every morning to keep the relative water content (RWC) of soil over 70 %], water-stress adapted (droughtadapted at 30 % relative soil water content for 30 days), and water stress without adaptation treatment (water-stressed to 30 % relative soil water content for 3 days). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
5
23
0
3
Order By: Relevance
“…As found also by other authors Medrano et al, 2002Medrano et al, , 2003Guan and Gu, 2009), the significant increase of NPQ found on WS-Sangiovese leaves compared to WSMontepulciano leaves indicates an elevated thermal dissipation of excessive excitation energy in the chloroplasts. On the other hand, NPQ covariate with the de-epoxidation state of the xanthophyll cycle similarly to what previously reported in grapevines (Chaumont et al, 1997;Flexas et al, 2000).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As found also by other authors Medrano et al, 2002Medrano et al, , 2003Guan and Gu, 2009), the significant increase of NPQ found on WS-Sangiovese leaves compared to WSMontepulciano leaves indicates an elevated thermal dissipation of excessive excitation energy in the chloroplasts. On the other hand, NPQ covariate with the de-epoxidation state of the xanthophyll cycle similarly to what previously reported in grapevines (Chaumont et al, 1997;Flexas et al, 2000).…”
Section: Discussionsupporting
confidence: 80%
“…Regardless of cultivar, the significantly lower values of J c , PSII and ETR found in leaves of stressed-vines are a common responses in grapevine and were reported for different varieties by several authors (Medrano et al, 2003;Guan et al, 2004;Guan and Gu, 2009;Beis and Patakas, 2012).…”
Section: Ww-vines Ws-vines Ww-vines Ws-vinesmentioning
confidence: 69%
“…Despite decreases in dry nodule weight, stomatal conductance and transpiration rate, the net photosynthetic rate did not differ from plants under water sufficiency. This may be associated with the elevation of photorespiration to preserve the photosynthetic apparatus, acting on dissipation of energy (Guan and Gu, 2009). Moreover, the genotypes R01-581F and R02-1325 showed higher concentration of chlorophyll under drought, whereas the other genotypes had a reduction, negatively affecting the photosynthetic performance (Baker and Rosenqvst, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Grapevines ( Vitis vinifera ) grow well in arid and semiarid environments (Cifre et al , Grimplet et al ), in spite of the fact that water limitations increase the hazards of photoinhibition (Lu and Zhang ). Several photoprotective mechanisms, including photorespiration, have been found to increase the sustainability of grapevines in these areas (Guan and Gu , Wang et al ).…”
Section: Introductionmentioning
confidence: 99%